Overclaim in Social Media and Online Reviews: Implications for Daviena Product Purchase Decisions Through Consumer Behavior - Nabilah Nabilah; Adhelia Qorimah Putri; Liestyaningrum Rahmadhani Wisnu Putri (LPPM Universitas Buddhi Dharma, 2025)
The rapid development of e-commerce and social media in Indonesia has shifted consumer purchasing behavior, especially in the skincare industry. Daviena Skincare, a local brand, has experienced significant growth through digital platforms such as TikTok and Shopee. However, increasing competition has led to the use of promotional strategies that include overclaims, exaggerated product benefits without scientific evidence which may mislead consumers. One controversy involving Daviena emerged when a TikTok content creator revealed discrepancies between claimed and actual ingredients in a product, triggering public concern and negative online discussions. In parallel, online customer reviews also play a critical role in shaping consumer trust and purchase decisions. This study aims to analyze the influence of overclaim in social media and online reviews on purchase decisions of Daviena Skincare products, with consumer behavior acting as a mediating variable. The research applies a quantitative approach using purposive sampling, with data collected through an online questionnaire involving 319 respondents who have seen Daviena promotions online. The analysis was conducted using SPSS. The results indicate that overclaim and online reviews significantly influence consumer behavior. However, both variables do not directly affect purchase decisions. Consumer behavior also does not have a significant direct effect on purchase decisions, suggesting that while awareness and perception are shaped, they may not result in action. These findings highlight the importance of ethical and transparent communication in digital marketing strategies.